Cell Death Related Proteins Beyond Apoptosis in the CNS - Bahatyrevich-Kharitonik, Bazhena; Medina-Guzman, Rafael; Flores-Cortes, Alicia; García-Cruzado, Marta; Kavanagh, Edel; Burguillos, Miguel Angel (Frontiers in Cell and Developmental Biology, 2022)
Cell death related (CDR) proteins are a diverse group of proteins whose original function was ascribed to apoptotic cell death signaling. Recently, descriptions of non-apoptotic functions for CDR proteins have increased. In this minireview, we comment on recent studies of CDR proteins outside the field of apoptosis in the CNS, encompassing areas such as the inflammasome and non-apoptotic cell death, cytoskeleton reorganization, synaptic plasticity, mitophagy, neurodegeneration and calcium signaling among others. Furthermore, we discuss the evolution of proteomic techniques used to predict caspase substrates that could potentially explain their non-apoptotic roles. Finally, we address new concepts in the field of non-apoptotic functions of CDR proteins that require further research such the effect of sexual dimorphism on non-apoptotic CRD protein function and the emergence of zymogen-specific caspase functions.